The presence of the Breviarius de Hierosolyma in Iona’s library - O'Loughlin, Thomas (Royal Irish Academy, 2012)
A comparative study of Adomnan (+704) writing about Jerusalem in his De locis sanctis with the anoymous work known as the Breviarius de Hierosolma shows that the the Breviarius was among the books that Adomnan consulted when he was writing his own guide to the Holy Places. While Adomnan is explicit that he had earlier books, he does not name any of them, but we can be certain from the overlapping items of information that the Breviarius was one of them. It was therefore one of the item in the monastery's library.